Personalized rock: A nostalgic fairground revival confection - Spence, C; Youssef, J (Elsevier, 2019)
Rock candy is a popular confectionary item and has long been associated with the seaside funfair here in the UK. One of the distinctive features of so-called fairground rock is that it requires careful (time-consuming and skilled) construction in order to deliver the eye appeal associated with having text running through the centre of each and every stick. This difficult-to-produce design feature is all about enhancing the eye-appeal – one might, in fact, think of it as ‘eye candy’ – since it presumably has no direct effect on the taste/flavour of the confection so produced. Our idea is to present small bite-sized pieces of seaside rock to give to the diners at the end of the fairground-inspired meal served by Kitchen Theory. This will enable the chef and his team to give the guest a personalized token that will hopefully trigger a positive sense of nostalgia, one that will last long after the meal is over. Given the technical challenges and time constraints involved in producing personalized lettered rock using traditional methods, a number of alternative solutions (involving different methods of production, or different forms of personalizing candy) are suggested. That said, an ideal solution has yet to be determined, given the various constraints (e.g., limited time and a focus on the quality/authenticity of the taste experience).